2007
DOI: 10.4049/jimmunol.178.2.748
|View full text |Cite
|
Sign up to set email alerts
|

The Extra Domain A from Fibronectin Targets Antigens to TLR4-Expressing Cells and Induces Cytotoxic T Cell Responses In Vivo

Abstract: Vaccination strategies based on the in vivo targeting of Ags to dendritic cells (DCs) are needed to improve the induction of specific T cell immunity against tumors and infectious agents. In this study, we have used a recombinant protein encompassing the extra domain A from fibronectin (EDA), an endogenous ligand for TLR4, to deliver Ags to TLR4-expressing DC. The purified EDA protein was shown to bind to TLR4-expressing HEK293 cells and to activate the TLR4 signaling pathway. EDA also stimulated the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 40 publications
2
115
0
Order By: Relevance
“…Thus, EDA stimulated the production by DC of proinflammatory cytokines, such as IL-12 or TNF-a and induced their maturation in vitro and in vivo. 17 With the aim of inducing anti-HPVE7 T cell responses, we fused HPVE7 to EDA and studied if the resultant recombinant fusion protein EDA-HPVE7 was able to bind to DC and induce their maturation. A control protein containing HPVE7 protein fused to a truncated version of the EDA (DEDA-HPVE7) lacking the first 50 aminoacids of EDA was also produced.…”
Section: Eda-hpve7 Fusion Protein Binds To Bone Marrow Derived Dcs Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, EDA stimulated the production by DC of proinflammatory cytokines, such as IL-12 or TNF-a and induced their maturation in vitro and in vivo. 17 With the aim of inducing anti-HPVE7 T cell responses, we fused HPVE7 to EDA and studied if the resultant recombinant fusion protein EDA-HPVE7 was able to bind to DC and induce their maturation. A control protein containing HPVE7 protein fused to a truncated version of the EDA (DEDA-HPVE7) lacking the first 50 aminoacids of EDA was also produced.…”
Section: Eda-hpve7 Fusion Protein Binds To Bone Marrow Derived Dcs Inmentioning
confidence: 99%
“…[17][18][19] Thus, in the present study, we decided to evaluate a therapeutic vaccine against cervical carcinoma based on the fusion protein EDA-HPVE7 containing EDA and the E7 protein from HPV16, which seems to be required together with E6 protein for onset 20 and maintenance 21 of malignant transformation. It was found that EDA-HPVE7 fusion protein can induce antitumor CD8 þ T cell responses in the absence of additional adjuvants and, when given in combination with the TLR ligands pIC or CpG, is able to eradicate large established HPVE7-expressing TC-1 tumors.…”
mentioning
confidence: 99%
“…Several other molecules like the scavenger receptor Lox-1 (11), the mannose receptor (12), some chemokine receptors (13,14), and TLRs (15,16) have been tested for their potential in immunotherapy. A critical lesson from all of these studies is that some receptors (4,5,11,12), but not others (16,17), require the addition of a DC maturation signal to induce protective immunity. Collectively, it is difficult to predict which strategy among the proposed ones is the most efficient on a comparative basis.…”
Section: Selection Of An Antibody Library Identifies a Pathway Tomentioning
confidence: 99%
“…Although information on the biological properties of EDA is limited, it is known that EDA induces NF-κ factor activation, which is involved in connective tissue destruction, tissue remodeling in response to chronic inflammatory lesion development, and in monocyte and dendritic cell migration throughout their basal membrane. These EDA associated effects are triggered in response to the interaction between EDA and its specific TLR-4, a receptor that also interacts with LPS of Gram negative bacteria [11,12]. Altogether, these observations suggest that the expression of EDA in response to tissue injury, or other cellular warning signals, might induce recruitment of dendritic cells to the site of injury and trigger their subsequent maturation.…”
Section: Introductionmentioning
confidence: 72%
“…Altogether, these observations suggest that the expression of EDA in response to tissue injury, or other cellular warning signals, might induce recruitment of dendritic cells to the site of injury and trigger their subsequent maturation. Indeed, previous work demonstrates that EDA, as fusion protein, may constitute a strategy to target viral or tumoral antigens to dendritic cells in vivo [11,13,14]. Therefore, the capacity of EDA to induce dendritic cell maturation through TLR4 activation may also favor antigen uptake, expression of co-stimulatory signals, antigen presentation and the induction of anti-viral or antitumoral T cell responses [11,13].…”
Section: Introductionmentioning
confidence: 99%